THE IMPLEMENTATION OF THE TAXONOMIC SPATIAL MEASURE OF DEVELOPMENT IN THE ANALYSIS OF CONVERGENCE IN THE STANDARD OF LIVING - Kuc, Marta (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The main goal of this paper is to analyze the existence of social convergence in the European Union in 1995-2012. The social convergence refers to a reduction in the dispersion of the standard of living across countries. A taxonomy spatial measure of development is used as the standard of living approximation. The use of a new approach proposed by E. Antczak allows explaining the disparities in the analyzed phenomenon by taking into account the immeasurable spatial factor. Variety techniques are used to test for convergence. The existence of sigma, beta and gamma convergence was tested for the global aggregated measure of the standard of living, as well as for 10 groups of factors affecting this phenomenon.